1995
DOI: 10.1002/1097-0142(19950115)75:2<518::aid-cncr2820750214>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Association of human leukocyte antigen-B1*03 with cervical cancer in Japanese women aged 35 years and younger

Abstract: Background. An association of human leukocyte antigen (HLA)‐DQw3 alleles with squamous cell carcinoma (SCC) of the cervix has been reported in some European populations, but the significance of HLA‐DQw3 has not been examined in other populations to the authors' knowledge. The interaction between HLA‐DQw3 and human papillomavirus (HPV) in SCC remains to be clarified. Methods. To elucidate the association of HLA‐DQ alleles with SCC of the cervix, DNA samples extracted from blood lymphocytes of 23 patients with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…To date, most studies have demonstrated that DQB1*03 (DQB1*0301, DQB1*0302, and DQB1*0303) is positively correlated with cervical cancer and increases its risk (Madeleine et al, 2002). This finding has been confirmed in populations in Norway (Helland et al, 1994), Japan (Nawa et al, 1995), France (Sastre-Garau et al, 1996), and an African American community (Gregoire et al, 1994). One study involving Spanish women in New Mexico also demonstrated that HPV16-positive cervical cancer patients exhibited increased DQB1*0303 expression (Apple et al, 1994).…”
Section: Introductionmentioning
confidence: 84%
“…To date, most studies have demonstrated that DQB1*03 (DQB1*0301, DQB1*0302, and DQB1*0303) is positively correlated with cervical cancer and increases its risk (Madeleine et al, 2002). This finding has been confirmed in populations in Norway (Helland et al, 1994), Japan (Nawa et al, 1995), France (Sastre-Garau et al, 1996), and an African American community (Gregoire et al, 1994). One study involving Spanish women in New Mexico also demonstrated that HPV16-positive cervical cancer patients exhibited increased DQB1*0303 expression (Apple et al, 1994).…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, identifying specific HLA types associated with CaCx and the genes that encode them, are likely to be useful in predicting the susceptibility towards CaCx that is intimately associated with HPV infections. Associations between HLA DQw3 (class II type molecule) and CaCx have previously been observed among African-American (Gregoire et al 1994), Caucasian (Wank and Thomssen 1991;Helland et al 1992;Montoya et al 1998), and Japanese ethnic populations (Nawa et al 1995). No such report exists on Indian women inspite of the fact that CaCx appears to be the major cancer burden in these women.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that women carrying HLA DQw3 antigen encoded by DQB1*03, are predisposed to develop CaCx (Wank and Thomssen 1991). While several reports have been put forward in support of this finding (Helland et al 1992(Helland et al , 1994Gregoire et al 1994;Odunsi et al 1995;Nawa et al 1995;Montoya et al 1998) there are contradictory reports that show no such association (Glew et al 1992(Glew et al , 1993Apple et al 1994;Allen et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Although the evidence for a link between HLA and cervical cancer is conflicting, it has recently been reported that certain HLA class II alleles and haplotypes are positively associated with cervical cancer whereas others are negatively associated, that is, protective. Studies have reported an increased risk for cervical cancer among certain ethnic groups for carriers of HLA-DRB1*1501 [7][8][9], DRB1*1101 [10], DQB1*03 [11][12][13][14], and DQB1*0601 [15]. Specific combinations of alleles or haplotypes, such as DRB1*1501-DQB1*0602 [16 -18] and DRB1*1101-DQB1*0301 [19,20], have also been reported to increase risk.…”
Section: Introductionmentioning
confidence: 99%